Stratigraphic Evidence for Early Martian Explosive Volcanism in Arabia Terra. Issue 15 (1st August 2021) - Whelley, Patrick; Matiella Novak, Alexandra; Richardson, Jacob; Bleacher, Jacob; Mach, Kelsey; Smith, Reagan N.
Abstract: Several large paterae in Arabia Terra are suggested to be calderas that produced colossal explosive eruptions (i.e., supereruptions). If these features are indeed explosive calderas, dispersion modeling suggests extensive ash deposits should be common throughout the region. However, such deposits have not previously been linked with the suggested calderas. Here, we describe layered deposits containing minerals both consistent with and diagnostic of altered volcanic ash throughout Arabia Terra. These deposits include Al‐dominant minerals such as montmorillonite, imogolite, and allophane among others. Altered ash deposits are found to thin (from 1‐km to 100‐m thickness) away from the suggested calderas. We estimate that the volcanic ash observed in Arabia Terra is the result of between 1, 000 and 2, 000 individual explosive eruptions over 500‐million years. Our observations support the hypothesis that Arabia Terra hosted supereruptions in the late Noachian‐early Hesperian that repeatedly blanketed the region with layers of ash. Plain Language Summary: Several large and deep craters in western Arabia Terra, Mars are thought to be explosive calderas, a type of volcano capable of producing supereruptions. If these craters are calderas, vast layers of volcanic ash should be common in Arabia Terra. While layered deposits have been observed previously in Arabia, until now, no deposits have been associated with the suggested calderas. We present mineral signatures of volcanic ash deposits that thin (from 1 km to 100 m thickness) away from the suggested calderas. Our observations support the idea that explosive calderas do exist in western Arabia Terra, and they produced thousands of super eruptions spread out over 500 million years of ancient Mars history. Key Points: Layered deposits are found at seven locations in Arabia Terra involving minerals consistent with or diagnostic of altered volcanic ash Volcanic ash deposits documented here thin away from previously suggested sources, consistent with supereruption model predictions Between 1 and 2 thousand caldera‐forming eruptions over 500 million years from western Arabia Terra are needed to produce the observed ash